Investigating the neurocognitive deficits associated with chronic drug misuse. - Rogers, R; Robbins, T (2001)
Cognitive deficits associated with the chronic abuse of drugs have important theoretical and clinical significance: such deficits reflect changes to the underlying cortical, sub-cortical and neuromodulatory mechanisms that underpin cognition, and also interfere directly with rehabilitative programs. Recent investigations have been made into the neuropsychology of chronic abuse of cannabis, stimulants and opiates. It is suggested that future progress in this area, involving developing advances in brain-imaging and neuropharmacology, will capitalize on experimental demonstrations of specific patterns of impairments in decision-making, attention and memory function.